Factors affecting environmental ethics behavior of undergraduate students - Likhit, Junkaew; Prayoon, Wongchantra; Suparat, Ongon; Kannika, Sookngam; Praimee, Uraiwan (International Journal of Evaluation and Research in Education (IJERE), 2025)
The research aimed to investigate the variables affecting undergraduate students’ environmental ethical conduct as well as the variables influencing the environmental ethical behavior of undergraduate students of various genders and academic years. In the topic of environmental education, year 1-4 pupils made up the research sample. A total of 231 people from Mahasarakham University’s Faculty of Environment and Resource Studies freely provided information. A survey was used as the research method to assess the variables influencing undergraduate students’ ethical conduct in the environment. Frequency, percentage, mean, standard deviation, and one-way ANOVA testing of hypotheses are the statistics used for the study. The factors affecting the undergraduate students’ overall environmental ethical behavior were found to be at the highest level, equal to 4.04. After examining each item, it was found that serving the public and keeping promises was equal to 4.86, followed by upholding universal ideals (¯x=4.22), a factor that involves avoiding punishment. fear of criminal and disciplinary penalty (¯x=4.11), conformity factor (¯x=4.02), reward-seeking factor (¯x=3.97), social responsibility compliance factor (¯x=3.74), and personal qualities (¯x=3.41) were the factors that had the smallest effect on the student’s environmental ethical behavior, in that order. At the 05 levels, several factors influenced learners of different genders’ environmental ethical behavior, and various factors affected the environmental.